Broken Acces Control pada Website: System Literature Review - Sri Anita (LPPM, 2025)
Technological developments that make it easier for organizations to carry out their operations are no longer difficult, through websites organizations can display their reputation, products, services and achievements through websites that can be accessed by the public 24 hours a day. However, there is a threat that the more famous a website is, the more vulnerable it is to becoming a target for attacks. Broken Access Control is one of the causes of websites becoming victims of defacement attacks which can be detrimental both financially and reduce reputation. In this article we will discuss the causes of websites becoming infected with outbreaks, how to prevent them, and technological proposals that have implemented AI to prevent them. The method used in the research is the System Literature Review method which has been carried out by previous researchers who have successfully applied AI technology to prevent Broken Access Control attacks. The results obtained from the development of prevention technology are satisfactory with the success of detecting and rejecting 100% of the 10 simulated attacks. It is important to protect websites because it affects reputation, financial loss, violations regarding personal data protection, and damage to organizational operations which will have very detrimental impacts in the short, medium and long term.